"BOUQUET MADE BY NAVOI" - Shahnoza Panjiyeva (Journals Park Publishing, 2022)
This article discusses not only the Uzbek, but also the "Majilis un-nafois" and "Nasoyim ul-muhabbat" by Alisher Navoi, the king of poetry of the whole Eastern world. Navoi's anthology "Navoiyning nigohi tushgan" co-authored by literary scholar Begali Kasimov, which gives a broader idea of these sources about 15th-century literary figures, sheikhs and saints, was analyzed.
Keywords: Tazkira, literary-critical views, types and genres, sheikhs